2002
DOI: 10.1046/j.1460-9568.2002.02080.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral axotomy induces only very limited sprouting of coarse myelinated afferents into inner lamina II of rat spinal cord

Abstract: Peripheral axotomy-induced sprouting of thick myelinated afferents (A-fibers) from laminae III-IV into laminae I-II of the spinal cord is a well-established hypothesis for the structural basis of neuropathic pain. However, we show here that the cholera toxin B subunit (CTB), a neuronal tracer used to demonstrate the sprouting of A-fibers in several earlier studies, also labels unmyelinated afferents (C-fibers) in lamina II and thin myelinated afferents in lamina I, when applied after peripheral nerve transecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
67
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 63 publications
9
67
0
3
Order By: Relevance
“…As such, it was thought that low-threshold A fibers directly innervate nociceptionspecific neurons in lamina I, resulting in the gating of nonnoxious stimuli to pain pathways. Although the evidence for A fiber sprouting has been shown to be subject to methodological bias by tracing procedures (Bao et al, 2002;Tong et al, 1999), neuropathy-induced increases in spinal GAP-43 expression still suggest that fiber sprouting occurs within the superficial dorsal horn. Spinal GAP-43 expression was previously reported to be regulated in unmyelinated fibers following nerve injury (Coggeshall et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…As such, it was thought that low-threshold A fibers directly innervate nociceptionspecific neurons in lamina I, resulting in the gating of nonnoxious stimuli to pain pathways. Although the evidence for A fiber sprouting has been shown to be subject to methodological bias by tracing procedures (Bao et al, 2002;Tong et al, 1999), neuropathy-induced increases in spinal GAP-43 expression still suggest that fiber sprouting occurs within the superficial dorsal horn. Spinal GAP-43 expression was previously reported to be regulated in unmyelinated fibers following nerve injury (Coggeshall et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings confirmed previous reports showing the transganglionic labelling of the substantia gelatinosa after the injection of CTB-HRP into injured, but not into intact peripheral nerves , Lekan et al, 1996, Bao et al, 2002. We also demonstrated that neonatal capsaicin treatment produced irreversible loss of small sensory ganglion neurons, and consequently a selective Cfibre deafferentation of the spinal dorsal horn.…”
Section: Discussionsupporting
confidence: 92%
“…It has also been suggested that this contributes to the development of chronic pain states , 1995, White, 2000. Recently, the sprouting hypothesis has been challenged by showing an increase in the proportion of CTB-horse radish peroxidase (HRP)-labelled small DRG neurons after peripheral nerve transection (Tong et al, 1999 and the co-localization of "injury peptides" such as vasoactive intestinal peptide (VIP) and galanin (GAL), characteristic of injured C-fibre DRG neurons, with choleragenoid in small sensory ganglion neurons and in their central terminations (Bao et al, 2002. Electron microscopic histochemical studies furnished direct evidence for the transport of CTB-HRP in unmyelinated dorsal root axons following peripheral nerve transection .…”
Section: Introductionmentioning
confidence: 99%
“…Tissue preparation and immuno-electron microscopy were conducted as described [50]. Briefly, adult mouse was anesthetized with 2% pentobarbital sodium then perfusion-fixed with cold solution containing 0.4% glutaraldehyde (Cat#16220; Electron Microscopy Sciences, Hatfield, PA), 4% PFA (Cat#157-8, Electron Microscopy Sciences) in phosphate buffer (PB; 0.1 M, pH 7.4).…”
Section: Immuno-electron Microscopymentioning
confidence: 99%